Cannon Ball Tree, Trinidad, B.W.I. - (:unkn) unknown (Pereira and Co., Ltd., Trinidad, 2010)
The Cannon ball tree is indigenous to South America and the South Caribbean. Its scientifc name is Couroupita guianensis. The tree produces a pink aromatic flower and bears large globose woody fruits which look like big balls hanging from a string. The hard shells of the fruits are sometimes used to make utensils in some cultures.(Rao Pulakhandam,n.d.)
Colour: Black and white; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Couroupita guianensis; Trees--Trinidad and Tobago; Cannon ball tree--Trinidad and Tobago